When novel sentences spoken or heard for the first time in the history of the universe are not enough: toward a dual-process model of language. - Van Lancker Sidtis D (International Journal of Language & Communication Disorders)
Although interest in the language sciences was previously focused on newly created sentences, more recently much attention has turned to the importance of formulaic expressions in normal and disordered communication. Also referred to as formulaic expressions and made up of speech formulas, idioms, expletives, serial and memorized speech, slang, sayings, cliches, and conventional expressions, non-propositional language forms a large proportion of every speaker's competence, and may be differentially disturbed in neurological disorders. This review aims to examine non-propositional speech with respect to linguistic descriptions, psycholinguistic experiments, sociolinguistic studies, child language development, clinical language disorders, and neurological studies. Evidence from numerous sources reveals differentiated and specialized roles for novel and formulaic verbal functions, and suggests that generation of novel sentences and management of prefabricated expressions represent two legitimate and separable processes in language behaviour. A preliminary model of language behaviour that encompasses unitary and compositional properties and their integration in everyday language use is proposed. Integration and synchronizing of two disparate processes in language behaviour, formulaic and novel, characterizes normal communicative function and contributes to creativity in language. This dichotomy is supported by studies arising from other disciplines in neurology and psychology. Further studies are necessary to determine in what ways the various categories of formulaic expressions are related, and how these categories are processed by the brain. Better understanding of how non-propositional categories of speech are stored and processed in the brain can lead to better informed treatment strategies in language disorders.